How The Impact Of Self Regulation On Fear Of Missing Out (FOMO) and Internet Addiction On Elementary School Pre Service Teacher Students? - T. Muhtarom (Universitas PGRI Yogyakarta, 2022)
The pattern of interaction and communication among young people is currently changing more towards digital communication with virtual social networks. Unfortunately, not many studies have been conducted to determine the relationship between the communication behavior patterns of social media networks and the fear of missing out. This study aims to determine whether there is an influence of student self-regulation on the variable level of internet addiction and fear of missing out on information. This research was conducted using a survey method, taking a sample of 208 active students at the University of PGRI Yogyakarta, the sample was taken using a simple random sampling technique from a population of 480 students, the data were analyzed using a simple linear regression technique. The results showed that self-regulation had no significant effect on the level of fear of missing out, but had a significant effect on the internet addiction variable. For further reasons and causes of these findings are described in the discussion.